Crimped fiber with controllable patterns fabricated via electrohydrodynamic jet printing. (5th October 2017) - Wu, Yang; Wu, Bin; Vijayavenkataraman, Sanjairaj; Wong, Yoke San; Fuh, Jerry Ying Hsi
Abstract: A regular pattern called crimp is an essential morphological feature of collagen fibers in native tendon. In this study, a crimped fiber writing process based on electrohydrodynamic jet printing (E-jetting) has been developed to fabricate fibers with crimped morphology. The effects of the key process parameters (i.e. segment length, stage speed and dwell time) on the fiber characteristics were investigated to obtain controllable and regular crimped fibers. The induced crimp angle (~ 15°) and fiber diameter (~ 45 μm) using the optimal process parameters were comparable to those in the native tendons (i.e. 13–17° and 15–30 μm, respectively). Mechanical testing showed that the crimped fibers exhibited an initial nonlinear region and a subsequent linear region with different Young's modulus (22.6 ± 2.2 MPa and 33.2 ± 6.5 MPa, respectively), while the straight fibers were found only with a linear region. Human tenocytes cultured on the crimped fibers exhibited the aligned morphology with a broader and controllable nuclei angle distribution, as compared to those on the straight fibers. This study indicates the capability of crimped fiber writing to create fibers with controllable crimped morphology and biomimetic mechanical behaviors, demonstrating its potential in application of tissue engineering. Graphical abstract: Highlights: Crimped fiber writing based on E-jetting was applied to print patterns with crimped morphology. Key process parameters (segment length, stage speed and dwell time) were studied. Printed fibrous morphologies imitate the crimps in the native tendons. Stress-strain curve of crimped fibers exhibited an initial nonlinear region. Crimped fibers were able to regulate cell alignment.